Greenhouse Thrips, Heliothrips haemorrhoidalis (Bouche) - Harold A. Denmark; Thomas R. Fasulo (EDIS, 2005)
This thrips was described by Bouché in 1833 from specimens taken from a greenhouse in Europe as Thrips haemorrhoidalis. Packard described this species for the first time from this country in 1870 and called it the greenhouse thrips. This thrips appears in the Common Names of Insects approved by the Entomological Society of America as the greenhouse thrips, Heliothrips haemorrhoidalis (Bouché). This document is EENY-075 (originally published as DPI Entomology Circular No. 64), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: February 1999. Revised: August 2004.